Geographic variation in management of gall-stones - Abbas, Hussain Taher (Karbala Journal of Medicine, 2021)
Abstract: Prospective study that includes 200 cases of gall stones that operated randomly over two years in mesalata central hospital in Libya (2007-2009).The patients are divided in two groups, early age group (17-39years) and middle, late age group(40-80 years).Most of cases at early adult life operated by prompt cholecystectomy Results: 110 (55%) of cases are presented between 17-39 years, 63(31.5%) of them below 30 years ,59 (of these 63 cases) are females, 20% of them without risk factors while all the 4 male cases are with strong risk factor. 161(80.5%) of cases are females and 39(19.5%) of them are males .95(59%) of female cases between 18 -39 years, and 59(37%) before 30 years. Obstructive jaundice is seen in 9(4.5%) cases of 200, 7(18 % of 39 male cases) cases of them are males. Acute pancreatitis are seen in 6 cases (3%), 4(2%, adjusted with gender) of them are females Only one case (0.6%) of pancreatitis and other one case (o.6%) of obstructive jaundice are seen in females at early adult life. 2(1%) cases are presented with carcinoma of gallbladder Symptomatic gallstone is disease of young females. Main risk factor of gallstone at early adult life is estrogen “the higher the estrogen for long time as in multiple pregnancies the more risk”. The other risk factors “except family factors” takes its rules later when the patient is more than 30 years old. Because we adopt the regime of prompt cholecystectomy in all cases of early adult life, the serious complication of disease is low (2%). The males cases are more likely to develop complications of obstructive jaundice than females.